Asymmetric synthesis of d-fagomine and its diastereoisomers - Davies, S; Fletcher, A; Kennedy, M; Roberts, P; Thomson, J (Elsevier, 2018)
A divergent strategy for the asymmetric syntheses of d-fagomine and three of its diastereoisomers has been developed. The diastereoselective conjugate addition of an enantiopure lithium amide to an α,β-unsaturated ester was used as the key step to install the correct configuration required for the C(5)-stereogenic centre within the targets. In situ enolate oxidation generated the corresponding anti-α-hydroxy-β-amino ester, which possessed the correct configuration required for the C(4)-stereogenic centre within both d-fagomine and d-3-epi-fagomine. Subsequent epimerisation of this key anti-α-hydroxy-β-amino ester upon oxidation and diastereoselective reduction gave the corresponding syn-α-hydroxy-β-amino ester, which possessed the correct configuration required for the C(4)-stereogenic centre within both d-4-epi-fagomine and d-5-epi-fagomine. Elaboration of both α-hydroxy-β-amino esters upon reduction to the corresponding aldehydes followed by aldol reaction generated the requisite C(3)-stereogenic centres within the target compounds, then cyclisation and deprotection gave the enantiopure iminosugars in good overall yields, as single diastereoisomers (>99:1 dr).